(untitled) (Conference Zone, 2021)
In this article, it is assumed that the type of interpersonal relationships determines the tactics and style of work of both the leader and the leader. However, the practical importance of knowing the psychological content and essence of these leadership styles is that each style has its own positive side, as a skilled leader educates himself, the best of which is especially about the team he leads. opinions and comments are given.